T-RFLP Fingerprinting Analysis of Bacterial Communities in Debris Cones, Northern Victoria Land, Antarctica - Abramovich, Reut Sorek; Pomati, Francesco; Jungblut, Anne D.; Guglielmin, Mauro; Neilan, Brett A. (Permafrost and Periglacial Processes, 2012)
ISSN:1045-6740 ISSN:1099-1530